Dramatherapy in an adapted school: what identity boxes reveal - Porrovecchio, Alessandro; Pruvost, Bérénice Mai (Frontiers in Education, 2025)
BackgroundDramatherapy is increasingly used in special education contexts to support young people facing academic, emotional, and social challenges. In France, Regional Institutions for Adapted Education (EREA—Etablissement Régional d'Enseignement Adapté) serve vulnerable adolescents, often stigmatized and marginalized in mainstream schooling. This study explores the use of identity boxes as both a research method and a therapeutic tool in such a context.AimsThe study investigates how identity boxes, integrated into a dramatherapy program, can foster emotional expression, self-reflection, and improved peer relationships among students in an adapted education setting.MethodsConducted as part of a research project, the intervention involved ten dramatherapy workshops led by a certified dramatherapist and conducted with two groups of final- and penultimate-year students. A control group, who did not take part in the workshops, nonetheless participated in two sessions dedicated to the construction of identity boxes, delivered as part of their visual arts classes. The study adopted an ethnographic approach, combining participant observation, semi-structured interviews, and the analysis of identity boxes and the associated narratives.ResultsStudents in the dramatherapy group demonstrated enhanced emotional introspection, more positive peer interactions, and a stronger sense of Self, while the control group showed fewer developments. The identity boxes served both as expressive objects and as reflective instruments, offering deep insights into students' evolving self-perception and experiences of inclusion.ConclusionsThis study highlights the value of combining dramatherapy and creative visual methods in special educational settings. It underscores the importance of arts-based interventions in fostering emotional wellbeing and inclusion for students with disabilities and social difficulties, suggesting future applications in similar institutional contexts.